COMPARISON OF TWO TECHNIQUES HAMSTRING MUSCLE STRETCHING NO GAIN FLEXIBILITY ARTICULAR (Fiep Bulletin - online, 2013)
The flexibility is the ability of a muscle-tendon unit to stretch, while a hinge moves in its range of motion (ROM) in a comfortable, painless and non constrained way. A stretching technique is the muscle energy that combines static stretching, isometric contraction and relaxation, followed by another static stretching; and the other one is the active stretching technique, which moves away from the source of muscle insertion. The aim of this study was to compare the effect of two immediate and acute stretching techniques (active stretching and muscle energy) of the hamstring muscles regarding the articular flexibility. The sample consisted of 19 people, aged 18-25 years, who were randomly divided into two groups, one of them performed the muscle energy technique and the other one performed the active stretching. The data were analyzed using ANOVA with repeated measures (for intragroup comparison) and unpaired t test (for comparison between groups). In all cases, the accepted level of significance was p
Keywords: Stretching exercises muscle; flexibility.